(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Principle of wet and dry drug collection is applied for collection of drugs while preparing any formulations i.e. wet state of drug is taken in double to its dry drug quantity but in case of exception, drug should be taken in wet state and also not taking in double to its prescribed quantity. Here, Vasa is mentioned as an exceptional drug for wet and dry drug collection principle. Hence, Vasa Ghrita were selected as a dosage form to validate this principle. Aim of present study was to validate the wet and dry drug collection principle in the preparation of Vasa Ghrita through quantitative estimation of Vasicine. Three samples of Vasa Ghrita were prepared as per the reference of Charaka Samhita from wet and dry state with equal quantity of Vasa and wet state and double quantity of Vasa. On comparing the data of three samples highest yield (94.16%) was found in Vasa Ghrita prepared from wet and equal quantity. The percentage of Vasicine was more in dry Vasa Panchanga (0.1914%) than wet state (0.0999%) in HPTLC quantification. Equal quantity and wet state of Vasa Ghrita showed more percentage of Vasicine (0.0032%) than dry state and equal quantity (0.0028%) while the percentage of Vasicine in wet state double quantity was in nearer range (0.0035%) to wet state and equal quantity of Vasa Ghrita. So, it can be concluded that Vasa should be used in wet state without taking in double quantity in Vasa Ghrita.